Engineering high α‐amylase levels in wheat grain lowers Falling Number but improves baking properties - Ral, Jean-Philippe; Whan, Alex; Larroque, Oscar; Leyne, Emmett; Pritchard, Jeni; Dielen, Anne-Sophie; Howitt, Crispin A.; Morell, Matthew K.; Newberry, Marcus (Wiley, 2016)
Late maturity α‐amylase (LMA) and preharvest sprouting (PHS) are genetic defects in wheat. They are both characterized by the expression of specific isoforms of α‐amylase in particular genotypes in the grain prior to harvest. The enhanced expression of α‐amylase in both LMA and PHS results in a reduction in Falling Number (FN), a test of gel viscosity, and subsequent downgrading of the grain, along with a reduced price for growers. The FN test is unable to distinguish between LMA and PHS; thus, both defects are treated similarly when grain is traded. However, in PHS‐affected grains, proteases and other degradative process are activated, and this has been shown to have a negative impact on end product quality. No studies have been conducted to determine whether LMA is detrimental to end product quality. This work demonstrated that wheat in which an isoform α‐amylase (TaAmy3) was overexpressed in the endosperm of developing grain to levels of up to 100‐fold higher than the wild‐type resulted in low FN similar to those seen in LMA‐ or PHS‐affected grains. This increase had no detrimental effect on starch structure, flour composition and enhanced baking quality, in small‐scale 10‐g baking tests. In these small‐scale tests, overexpression of TaAmy3 led to increased loaf volume and Maillard‐related browning to levels higher than those in control flours when baking improver was added. These findings raise questions as to the validity of the assumption that (i) LMA is detrimental to end product quality and (ii) a low FN is always indicative of a reduction in quality. This work suggests the need for a better understanding of the impact of elevated expression of specific α‐amylase on end product quality.